(untitled) (Biological Sciences - PJSIR, 2002)
Celluose-based derivatives have been used in drilling fluids as viscosifiers and fluid loss reducers for many years. But more recently due to evident advantages, such as technology and relative ease of large-scale production of cellulose derivatives as powders or granules and the generally non-toxic nature of cellulose ethers, research efforts have been intensified to optimize their possible applications as polymer flooding materials in enhanced oil recovery. Consequently, this paper addresses the synthesis and characterization of polyacrylamide-sodium carboxymethyl cellulose graft polymer produced from locally available cellulose material. Notable improvement was achieved in the specific viscosity of he graft polymer when compared with the unmodified sodium carboxymethyl cellulose (NaCMC). For a I% (wt%) solution at 25°C and a shear rate of 200s·1, NaCMC has a viscosity of 74.6 centipose while the graft polymer recorded a viscosity of 154 centipose. The influence of mono and multivalent cations such as sodium, calcium and alumunium ions on the viscosity of the graft polymer solution was relatively minimal, suggesting improvement in the so-called salt tolerance or cation compatibility .